2009
DOI: 10.1590/s0103-21002009000800003
|View full text |Cite
|
Sign up to set email alerts
|

Co-morbidades e mortalidade de pacientes com doença renal: atendimento terceirizado de nefrologia

Abstract: Objectives: To identify the causes of co-morbidities and mortality among patients with renal disease who attended the SARA clinic in 2007, and to examine the relationships among personal factors, comorbidities, and risk factors for mortality. Methods: This descriptive retrospective study reviewed medical records of 232 patients with acute renal failure (ARF) on hemodialysis. Results: The majority of patients were males (60.3%). A greater number of them were between 61 to 80 years old (37%) and the hemodialysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
14

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 1 publication
(2 reference statements)
1
1
0
14
Order By: Relevance
“…(Leiser, Tognim, & Bedendo, 2007) The predominance of infected patients admitted to the intensive care unit (ICU), the prevalence of very old male individuals was similar to previous studies (Grothe, Belasco, Bitencourt, Vianna, Sesso, & Barbosa, 2010;Moreira, Borges, Costa, Quinino, Serra, & Oliveira, 2008) The diabetic patients undergo constant changes and complications of disease, including risk of developing nephropathy (Oliveira, Alves, & Bezerra, 2009). Our study, however, found no relationship between kidney disease and this disease.…”
Section: Discussionsupporting
confidence: 90%
“…(Leiser, Tognim, & Bedendo, 2007) The predominance of infected patients admitted to the intensive care unit (ICU), the prevalence of very old male individuals was similar to previous studies (Grothe, Belasco, Bitencourt, Vianna, Sesso, & Barbosa, 2010;Moreira, Borges, Costa, Quinino, Serra, & Oliveira, 2008) The diabetic patients undergo constant changes and complications of disease, including risk of developing nephropathy (Oliveira, Alves, & Bezerra, 2009). Our study, however, found no relationship between kidney disease and this disease.…”
Section: Discussionsupporting
confidence: 90%
“…Os motivos para a internação dos pacientes incluem causas renais e sistêmicas associadas, como hipertensão arterial, diabetes mellitus, lúpus e infecções 6 . O número de novos casos estimado para a Região Nordeste, em 2011, foi de 6001 pacientes e vem aumentando a taxa de incidência ao longo dos anos 7 .…”
Section: Revisão De Literaturaunclassified
“…As complicações mais comuns durante a hemodiálise são, em ordem decrescente de frequência, hipotensão (20%-30% das diálises), cãibras (5%-20%), náuseas e vômitos (5%-15%), cefaleia (5%), dor torácica (2%-5%), dor lombar (2%-5%), prurido (5%), febre e calafrios (< 1%). As complicações menos comuns, mas sérias e que podem levar à morte incluem: a síndrome do desequilíbrio, reações de hipersensibilidade, arritmia, hemorragia intracraniana, convulsões, hemólise, embolia gasosa, hemorragia gastrintestinal, problemas metabólicos, convulsões, espasmos musculares, insônia, inquietação, demência, infecções, pneumotórax ou hemotórax, isquemia ou edema na mão e anemia [1,[3][4][5][6][7][8][9][10][11].…”
Section: Introductionunclassified